The Application of Restorative Justice in Traffic Accidents with Child Perpetrators that Resulted in The Death of The Victim - Rahtami Susanti; Yusuf Saefudin (Proceedings Series on Social Sciences & Humanities, 2023)
The basic principle of restorative justice in the case of an accident that resulted in the death of the victim is the recovery of the victim's heirs who suffered from the death of the victim. The perpetrator's family and the victim's family make an agreement in the form of compensation to the victim's family. This research examines the settlement of traffic accident cases with the principle of restorative justice in Law Number 22 of 2009 concerning Road Traffic and Transportation and the application of the principle of restorative justice in the examination of cases in court in cases of traffic accidents committed by children resulting in death. The research method is normative juridical. The results showed that Law Number 22 of 2009 concerning Road Traffic and Transportation requires compensation to be given to the victim's family where in the perspective of restorative justice this is in line with the recovery of losses suffered by the victim's family. If the perpetrator is a child, the settlement uses diversion if there is an agreement between the parties. If no agreement is reached, the examination continues in court where the judge still prioritizes the principles of restorative justice in examining and passing a verdict.